O setor privado e a educação superior brasileira no governo Lula e Dilma - Silva, Vanuzia Pereira da (2019)
The problems of high education in Brazil caused intense discussions about expansion process at the beginning of the 21st century. During this period, proposals, suggestions and solutions were proposed to massify education through the participation of the private sector, based on the constant influence of multilateral organizations. This massification served as a strategy to qualify the Brazilian workforce at the same time as the State promoted public policies for access to higher education, such as the University for All Program (Prouni), the Student Financing Fund (FIES) and the Restructuring and Expansion of the Federal Universities (Reuni), has made these private institutions look to education as a sector with a growing and profitable demand. This dissertation aims to present how the private sector consolidated its logic in Brazilian higher education in the Luis Inacio Lula (2003 – 2010) and Dilma Roussef (2011 – 2016) government, opening space for the formation of large educational conglomerates through the mergers and acquisitions of private education institutions. In the present work, this process of expansion of private education will be presented through the influence of multilateral organizations and Brazilian governments, analyzing the growth of the enrollment rate, number of students, campus, evolution in the number of private institutions, equity and besides will point out the main mergers and acquisitions of the private educational sector. For this, a bibliographical review is made and indicators of the educational sector are used as sources of information